SKEMA TRANSFER PRICING UNTUK PENGALIHAN LABA - Pratikto Winardi Bakhram; Hermanto Siregar; Moch Hadi Santoso (School of Business, Bogor Agricultural University (SB-IPB), 2021)
More than 60% of world transactions used a transfer pricing scheme. Transfer pricing for tax avoidance is not in accordance with domestic Indonesian tax rules. This study aim to generate understanding about transfer pricing concept, determine transfer pricing risk factors, identify transfer pricing schemes, and explain transfer pricing risk management. Descriptive analysis method based on secondary data and literature studies applied in this research. This research shows that transfer pricing should be based on the arm’s length principle. Factors that determine transfer pricing risks are inter-company transactions, tax rates, and foreign ownership. Transfer pricing can be implemented in inter-company transactions schemes related to sales, intangible asset, loan and services through one or a combination of several types of inter-company transactions. Transfer pricing risk management can be carried out through law enforcement, access of information agreement, and development of a transfer pricing risk-based monitoring system. The Directorate General of Taxes needs to pay attention to taxpayers who have affiliated transactions, lower tax rates, and foreign ownership in monitoring the risk of transfer pricing. Business groups also need to to fulfill the arm's length principle in the transfer pricing scheme in order to comply with the regulation. Keywords: business groups, inter-company transactions, profit shifting, tax avoidance, transfer pricing